An Assessment of the Impact of Target Costing on the Financial Performance of South African State-Owned Entities - Mchavi, Nyiko D.; Ngwakwe, Collins C, (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
This paper examines the effect of target costing on the financial performance of state-owned enterprises (SOEs). The paper aims to clarify the impact of this strategic cost management technique, particularly target costing on financial performance variable. The result of the study highlights an increasing importance of target costing in improving organisational profitability by depicting a favourable association between target costing and financial performance. This paper enhances the current knowledge base by investigating the particular setting of state-owned enterprises (SOEs) and analysing the possible moderating variables that might affect the link between target costing and financial success. Moreover, this paper provides significant insights for policymakers and practitioners in state-owned enterprises aiming to enhance their financial performance via strategic cost management.